Catification : designing a happy and stylish home for your cat (and you!) - Galaxy, Jackson (Jeremy P. Tarcher/Penguin, 2014)
"Cat owners know the struggles of creating living spaces that are both functional and stylish for owner and cat. In Catification, Jackson Galaxy, the star of Animal Planet's My Cat from Hell, and Kate Benjamin, of the popular cat design website Hauspanther.com, walk readers through a step-by-step process of designing an attractive home that is also an optimal environment for cats"--